Ultrasonic abrasive polishing of additive manufactured parts: An experimental study on the effects of process parameters on polishing performance - Wang, Jingsi; Liu, Xiaolong; Liew, Pay Jun; Zhu, Jiaqi; Li, Changhe; Huang, Chuanzhen (Chair of Production Engineering (CPE), 2022)
The rough surface of metal parts produced by the powder-based layered Additive Manufacturing (AM) technology such as Selective Laser Melting (SLM) is an important problem that needs to be solved. This study introduces obvious improvements in the surface quality of the AM parts by means of ultrasonic abrasive polishing (UAP), which uses cavitation collapse and micro-cut of abrasive particles for finishing surfaces. Experiments were conducted using the orthogonal experimental design method with an L9(34) orthogonal array to investigate the effects of ultrasonic power, machining time, abrasive particle size, and particle concentration on surface roughness Ra and material removal rate (MRR). The wear of the abrasive particles in the slurry was also studied. IN625 nickel-based alloy specimen manufactured by Selective Laser Melting (SLM) was chosen as the target workpiece. The results show that when the ultrasonic output power was too high, both surface quality and machining efficiency were deteriorated. And the surface roughness Ra was not further improved by just increasing the machining time. Severe cavitation erosion occurred in the polishing process and created leftover pits on the workpiece surface, which has a large influence on Ra. The size and amount of the abrasive particles should be within a certain range, which is helpful for material removal and improving the polishing performance. The work is useful for studying the influential process parameters involved in UAP and finding out the appropriate conditions.